Comparison of different irrigants in the removal of endotoxins and cultivable microorganisms from infected root canals - Valera, Marcia Carneiro [UNESP]; Cardoso, Flávia Goulart da Rosa [UNESP]; Chung, Adriana [UNESP]; Xavier, Ana Cláudia Carvalho [UNESP]; Figueiredo, Mariana Diehl [UNESP]; Martinho, Frederico Canato [UNESP]; Palo, Renato Miotto [UNESP] (Wiley, 2015)
This study was conducted to compare the effectiveness of different irrigants used to remove endotoxins and cultivable microorganisms during endodontic therapy. Forty root canals were contaminated and divided into groups according to the irrigant: 2% NaOCl + surfactant, 2% CHX, 2.5% NaOCl, and pyrogen-free saline solution (control). Samples were collected after root canal contamination (S1), after instrumentation (S2), and 7 days after instrumentation (S3). Microorganisms and endotoxins were recovered from 100% of the contaminated root canals (S1). At S2, 2% NaOCl + surfactant, 2% CHX, and 2.5% NaOCl were able to completely eliminate cultivable microorganisms. At S3, both 2% CHX and 2.5% NaOCl were effective in preventing C. albicans and E. coli regrowth, but E. faecalis was still detected. No microorganism species was recovered from root canals instrumented with 2% NaOCl + surfactant. At S2, a higher percentage value of endotoxin reduction was found for 2% NaOCl + surfactant (99.3%) compared to 2% CHX (98.9%) and 2.5% NaOCl (97.18%) (p < 0.05). Moreover, at S3, 2% NaOCl + surfactant (100%) was the most effective irrigant against endotoxins. All irrigants tested were effective in reducing microorganisms and endotoxins from root canals. Moreover, 2% NaOCl + surfactant was the most effective irrigant against endotoxins and regrowth of microorganisms.